EFEKTIVITAS PENERAPAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI STUDY KASUS TOKO PLASTIK GENTONG SAKTI KEDIRI - Dewi, Novi Fitriana; Zulistiani, Zulistiani; Damayanti, Susi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The purpose of this study was to find out and analyze how effective the application of work discipline is on the performance of employees at the Gentong Sakti Kediri plastic shop. This type of research is a descriptive study using a qualitative approach. Data collection techniques are by observing, interviewing and documenting. The informants in this study were shop owners, 2 employees and 2 buyers. Based on the results of the study it was concluded that the lack of discipline among employees at the Gentong Sakti Kediri store was due to a lack of cooperation between employees which caused social jealousy among fellow employees which triggered conflict within the company.